Serviços ecossistêmicos do telhado verde: regulação do ciclo hidrológico e manutenção da biodiversiade urbana - Lopes, Ely Ewerton Amorim (2022)
Urbanization drastically alters the environment, especially in countries of the Global South marked by processes of disordered urban densification. Green roofs are a way to partially recover lost ecosystem services, such as regulating the hydrological cycle or maintaining urban biodiversity. However, the application of this technology is still not very expressive in Brazil, especially in the northeast region. In this sense, the study had four objectives: 1) evaluate the life cycle and reproductive and vegetative phenology of ruderal species on extensive green roofs; 2) evaluate the influence of the proximity of forest remnants on the biodiversity of floral visitors and the performance (growth and flowering) of ruderal species on green roofs; 3) investigate the retention capacity of the precipitated volume; 4) investigate the perception of civil construction professionals about green roofs, applicability and ecosystem services provided. Prototypes of green roofs measuring 4.8 m² were installed in four districts of João Pessoa with different configurations of forest fragments in the surroundings, called green and grey scenarios. Two ruderal plants were used, Tridax procumbes and Richardia grandiflora, containing five replicas of each species per prototype. The vegetative and reproductive performance of the vegetation cover was monitored by semi-quantitative evaluations and aerial image analysis. The biodiversity of floral visitors was accompanied by naturalistic observations by the individual-focal method. The hydrological performance of green roofs was measured by the volume of rainfall retained on a daily scale. In addition, the perception of construction professionals about green roofs was evaluated through questionnaires. The ruderal plants R. grandiflora and T. procumbes showed good performance in the rainy season, with rapid growth and abundant flowering. They did not withstand the dry period. However, their reproductive strategy provided the creation of a seed bank that allowed the spontaneous repopulation of the green roofs. The presence of green roofs proved important in attracting pollinators, suggesting that they can act as a supplementary niche for species, especially in greener areas that generally support a greater diversity of floral visitors. The green roofs showed a retention capacity greater than 50% for daily rainfall of up to 40 mm/day, negatively influenced by the increase in precipitation volume and by the condition of previous rainy days. In addition, the type of vegetation cover did not cause differences in hydrological performance. For more intense rainfall (>40 mm), the integration of other flow control measures at the source is indicated. Construction professionals reported little familiarity with green roofs, in addition to low demand and supply for the service in the city, being the most active architects. The most relevant ecosystem services were thermal and hydrological regulation. The main difficulties pointed out were the lack of customer interest and technical information, having as ways of improvement activities to raise awareness of the population and inclusion of the topic in university curricula, and the creation of government incentives.